Antimicrobial Susceptibility of Enterococcus faecium Isolated from Bee-gut on PhzM Gene of Pseudomonas aeruginosa Isolates from Infected Wounds - Waheed Anwer, Amna; Mohamed Saleh, Ghada; Emad Ahmed, Mais Emad Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The aim of this study was to isolate and characterize Fructophilic lactic acid bacteria (FLAB) species from the honeybee gut. Based on the results of this study, it was found that the FLAB species obtained from honey were Gram-positive and catalase-negative, and this identification was confirmed through 16S rRNA gene sequencing. The researchers performed a primary screening to evaluate the effect of the cell-free supernatant (CFS) obtained from Enterococcus faecium (E5), and it was observed that the CFS showed a high inhibition zone of 23 mm against multidrug-resistant Pseudomonas aeruginosa, as determined by the agar well diffusion assay. This study also conducted further investigation to determine the optimal conditions for the production of cell-free supernatant (CFS). The results indicated that yeast extract was the most effective nitrogen source, while glucose was the preferred carbon source for CFS production. The optimal pH for CFS production was 5, and the incubation period of 72 hours was determined to be the most suitable for obtaining a high yield of CFS. Another aspect of the study aimed to identify multidrug-resistant Pseudomonas aeruginosa isolates from burn wound infections. The isolates were identified using the VITEK 2 system, and the presence of the phzM gene was detected in all nine strains. Furthermore, the study evaluated the effect of the cell-free supernatant (CFS) of the selected strain (E5) on the expression of the phzM gene. According to the study, the cell-free supernatant (CFS) significantly decreased the expression of the phzM gene in isolates of multidrug-resistant Pseudomonas aeruginosa. Enterococcus faecium could be a useful antimicrobial agent for treating P. aeruginosa infections that are resistant to multiple drugs.